When Film Mediatizes Taoism, What Does It Bring to Taoism? - Sun, Zhentao (Religions, 2023)
Although Taoism is no longer what it was in its prime, Taoist culture still has great spiritual value in the present day and is well worth promoting worldwide. Taoist cinema plays a powerful role in the mass communication of Taoism. Current academic research on Taoist cinema has focused on analyzing how it can make good use of Taoism but has neglected to explore what cinema brings to Taoism in the cinematization process. This paper focuses on this thesis by considering the themes of the importance of the cinematization of Taoism for Taoism, the cultural transformation in the cinematization of Taoism, and the appropriate way to include Taoism in Taoist films. This paper indicates that Taoist cinema has communicated Taoist ideology, religious rituals and aesthetic styles to a global audience through the audiovisual language, and it has built a bridge between Taoism and the general public. In the cinematization of Taoism, in order to reflect the communication environment, communication media and audience influence, Taoist films have highlighted visual spectacles, entertainment and popularization, thus making them better accepted by audiences and achieving the expected communication effect. This paper argues that Taoist films express the sacred and exert a religious influence on the viewer through content rather than transcendental style.